Friendship network characteristics and psychological well-being in late adolescence: Exploring differences by gender and gender composition. Issue 2 (March 2014) - Almquist, Ylva B; Östberg, Viveca; Rostila, Mikael; Edling, Christofer; Rydgren, Jens
Aims : The aim of the present study was to examine the association between friendship networks and psychological well-being among 19-year-olds. Methods : The data used was a random sample of Swedish individuals born in 1990 who answered a questionnaire in 2009–2010. Friendship networks were considered in terms of three measures of emotional support. Six statements about the individual's emotional state were used to create a summary measure of psychological well-being. Gender and gender composition were included as potentially moderating factors. The association between friendship networks and psychological well-being was analysed by means of linear regression analysis ( n = 1289). Results : The results indicate that males' and females' friendship networks were similar with regard to quality and trust, whereas males' networks were characterized by less self-disclosure and a stronger preference for same-gender friendships. Gender composition did not matter for the support levels. Emotional support was associated with psychological well-being but there were gender differences: females seemed to benefit more health-wise from having high-quality (and trusting) networks. Moreover, whereas self-disclosure among males was positively linked to well-being, this was not the case among females. None of these associations were moderated by gender composition. Conclusions : In sum, friendship networks are beneficial for the psychological well-being among late adolescents, but there are some important differences according to gender.